Reactogenicity and Immunogenicity of the Pfizer and AstraZeneca COVID-19 Vaccines - Mahallawi, Waleed H.; Mumena, Walaa A. (Frontiers in Immunology, 2021)
Background: The relationships of the coronavirus disease 2019 (COVID-19) vaccination with reactogenicity and the humoral immune response are important to study. Saudi Arabia was one of the first countries to implement a COVID-19 vaccination program, and the current study aimed to assess the reactogenicity and immunogenicity of the Pfizer and AstraZeneca COVID-19 vaccines among adults in Madinah, Saudi Arabia after receiving both doses. Methods: A cross-sectional study, including 365 randomly selected adult Pfizer or AstraZeneca vaccine recipients who received a homologous prime-boost vaccination. An electronic survey was sent to the vaccine recipients one week following receipt of the ﬁrst vaccine dose to collect data regarding sociodemographics and reactogenicity and invite them to participate in the collection of a blood sample. The reactogenicity data described in the current study involved the self-reported local and systemic symptoms experienced during the 7 days following the administration of the first vaccine dose. An evaluation of seropositivity for anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies was assessed using enzyme-linked immunosorbent assay (ELISA). Results: Among the participants, 69% (n = 250) reported at least 1 vaccine-related symptom. Pain at the injection site was the most frequently reported vaccine-related symptom. Significantly, a higher proportion of participants who received the AstraZeneca vaccine experienced headache, fever, pain injection site, and nausea compared with participants who received the Pfizer vaccine (p < 0.05). The mean total score for vaccine-related symptoms was significantly higher among participants who received the AstraZeneca vaccine, women, and participants with no previous COVID-19 infection (p < 0.05). Spike-specific IgG antibodies were detected in 98.9% of participants after the receipt of 2 vaccine doses, including 99.5% of Pfizer vaccine recipients and 98.3% of AstraZeneca vaccine recipients. Conclusion: Participants who received the Pfizer COVID-19 vaccine reported fewer vaccine-related complications compared with those who received the AstraZeneca COVID-19 vaccine, but no serious side effects were reported in response to either vaccine. Health status and age were factors that may influence COVID-19 vaccine effectiveness for the generation of antibodies against the SARS-CoV-2 spike protein.